PENGARUH DIGITALISASI TERHADAP KETAHANAN PANGAN: ANALISIS REGRESI SPASIAL DI PROVINSI JAWA TIMUR - Hasanah, Julita; Rahmatin, Miskah Aini; Syah, Mohammad Firman; Handayani, Rizky Noer; Supriono, Agus (Lampung University, 2025)
The era of globalization and digitalization has brought significant disruption to global food systems, including in Indonesia. Multidimensional challenges such as climate change, environmental degradation, and global food price volatility have increased the urgency of designing adaptive, and region-based food security strategies. This study aims to analysed the key determining factors of food security from the perspectives of digital technology and the green economic principles across 36 regencies and cities in East Java Province. Spatial regression analysis was employed to examine the impact of selected variables and capture spatial interdependence among regions. The results reveal that the Indonesia Digital Society Index, particularly the pillars of infrastructure (β = 0.3355) and ecosystem (β = 0.0015), has a positive and significant impact on improving the Food Security Index. Conversely, the digital job pillar shows a negative association (β = -0.4927), suggesting that the rise of digital employment may not align with local food security efforts. Additionally, premium and medium rice prices positively influence food security, while local soybean prices have a negative effect. The spatial lag coefficient (ρ = 0.6361) confirms that the existence of positive spatial autocorrelation, indicating that neighbouring regions tend to influence each other's food security dynamics. These findings emphasize the need for regional food security strategies that integrate digital transformation with green economic principles. Policy implications include strengthening digital infrastructure, fostering interregional collaboration, ensuring equitable digital access, and promoting environmentally sustainable agriculture—aligning with Indonesia’s long-term vision for a resilient, inclusive, and adaptive food system. Key words: digital transformation; food security; green economy; spatial analysis